Developing an Evaluation Framework for Consumer-Centred Collaborative Care of Depression Using Input from Stakeholders. (March 2013) - McCusker, Jane; Yaffe, Mark; Sussman, Tamara; Kates, Nick; Mulvale, Gillian; Jayabarathan, Ajantha; Law, Susan; Haggerty, Jeannie
Objective: To develop a framework for research and evaluation of collaborative mental health care for depression, which includes attributes or domains of care that are important to consumers. Methods: A literature review on collaborative mental health care for depression was completed and used to guide discussion at an interactive workshop with pan-Canadian participants comprising people treated for depression with collaborative mental health care, as well as their family members; primary care and mental health practitioners; decision makers; and researchers. Thematic analysis of qualitative data from the workshop identified key attributes of collaborative care that are important to consumers and family members, as well as factors that may contribute to improved consumer experiences. Results: The workshop identified an overarching theme of partnership between consumers and practitioners involved in collaborative care. Eight attributes of collaborative care were considered to be essential or very important to consumers and family members: respectfulness; involvement of consumers in treatment decisions; accessibility; provision of information; coordination; whole-person care; responsiveness to changing needs; and comprehensiveness. Three inter-related groups of factors may affect the consumer experience of collaborative care, namely, organizational aspects of care; consumer characteristics and personal resources; and community resources. Conclusion: A preliminary evaluation framework was developed and is presented here to guide further evaluation and research on consumer-centred collaborative mental health care for depression.